Estimation ESTIMATION OF TIN RESOURCES USING INVERS DISTANCE WEIGHTED (IDW) AND NEAREST NEIGHBOR POINT (NNP) METHODS IN BANGKA TENGAH DISTRICT, BANGKA BELITUNG ISLANDS PROVINCE : Estimation of tin resources - RAHUL GONZALES; Rahardi, Muhammad Rafif Gusvi; Adree Octova (EarthCare, 2024)
Indonesia is a country rich in tin minerals. Indonesia has 17% of the world's total tin reserves but produces 26% in 2020. This shows an unequal value between income and expenditure. Therefore it is necessary to calculate tin resources on a regular basis so that their availability is maintained. Here, two methods of calculating the estimated tin resources are used, namely the inverse distance weighted (IDW) and nearest neighbor point (NNP) methods. The estimation results using both methods are tin resources using the IDW method of 1,501,300 tons while using the NNP method 1,270,222 tons. In conclusion, there is a difference in the estimation results using the two methods of 231,078 tons or 18%. This difference is caused by the working of the two methods, namely the principle IDW method considers several closest points, while the NNP method considers the closest point.